"Religion and Nation Are One": Social Identity Complexity and the Roots of Religious Intolerance in Turkish Nationalism. Issue 2 (9th April 2018) - Goalwin, Gregory J.
Abstract : Turkish nationalism has long been an enigma for scholars interested in the formation of national identity. The nationalist movement that succeeded in crafting the Republic of Turkey relied upon rhetoric that defined the nation in explicitly secular, civic, and territorial terms. Though the earliest scholarship on Turkish nationalism supported this perspective, more recent research has pointed to Turkey's efforts to homogenize the new state as evidence of the importance of ethnicity, and particularly religion, in constructing Turkish national identity. Yet this marked mismatch between political rhetoric and politics on the ground is perplexing. If Turkey was meant to be a secular and civic state, why did Turkish nationalist policies place such a heavy emphasis on ethnic and religious purity? Moreover, why did religious identity become such a salient characteristic for determining membership in the national community and for defining national identity? This article draws upon historical research and social identity complexity theory to analyze this seeming dichotomy between religious and civic definitions of the Turkish nation. I argue that the subjective overlap between religious and civic ingroups during the late Ottoman Empire and efforts by nationalists to rally the populace through religious appeals explains the persistence of religious definitions of the nation despite the Turkish nationalist movement's civic rhetoric, and accounts for much of the Turkish state's religiously oriented policies and exclusionary practices toward religious minorities in its early decades.